1984
DOI: 10.1007/bf00542140
|View full text |Cite
|
Sign up to set email alerts
|

Changes in circulating thyroid hormones during short-term hepatic enzyme induction with carbamazepine

Abstract: The effect of short-term hepatic enzyme induction with carbamazepine (CBZ) on circulating thyroid hormone concentrations was studied in 10 healthy male subjects. CBZ 400 mg per day was given for 21 days in 6 subjects and for 14 days in a further 4. In the former group the effect of therapy on the pituitary/thyroid axis was also assessed by measuring thyroid stimulating hormone (TSH) response to thyrotrophin-releasing hormone. CBZ therapy resulted in induction of hepatic monooxygenase activity, evidenced by a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
20
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 9 publications
7
20
0
Order By: Relevance
“…The finding of low serum T 4 and fT 4 concentrations in epileptic patients receiving CBZ is coherent with earlier reports (12,13,(19)(20)(21)(22)(23)(24)(25)(26). The large majority of these studies and also our data demonstrate that serum T 4 and fT 4 decreased whereas TSH levels remained unchanged.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The finding of low serum T 4 and fT 4 concentrations in epileptic patients receiving CBZ is coherent with earlier reports (12,13,(19)(20)(21)(22)(23)(24)(25)(26). The large majority of these studies and also our data demonstrate that serum T 4 and fT 4 decreased whereas TSH levels remained unchanged.…”
Section: Discussionsupporting
confidence: 82%
“…Blank and Joffe (33,45) suggested that CBZ may alter thyroid hormone levels affecting directly TSH or TRH, but our data do not support this possibility. In agreement with other authors (5,19,26), TSH levels do not increase in CBZ-treated patients, the cause is not activated by the positive feedback mechanism, which should result from low serum thyroid hormone concentrations and serum thyroid hormone levels remain low. Moreover, TRHstimulated secretion of TSH is not increased during CBZ medication.…”
Section: Discussionsupporting
confidence: 76%
“…(1 2-14, 16,19,20,22,[23][24][25]27) T,, triiodothyronine; T,, thyroxine; IT4, free thyroxine, TSH, thyroid-stimulating hormone; TBG, thyroxine-binding globulin; CBZ, carbamazepine; VPA, valproate; PB, phenobarbital.…”
Section: Discussionmentioning
confidence: 99%
“…E-mail: pdcastro@uscmail.usc.es marked protein-binding activity, such as DPH and carbamazepine (CBZ) ( 3 3 , typically cause reduced levels of thyroxine (T,) and free thyroxine (FT,), but have variable effects on triiodothyronine (T3), free triiodothyronine (FT,), and thyroxine-binding globulin (TBG) levels, and no effect on TSH levels (12-14, 16,19,20,[22][23][24][25]. The effects of AEDs with enzyme-inducing activity but only weak protein-binding activity, such as phenobarbital (PB) (36,37), are typically similar to those of DPH and CBZ, although of smaller magnitude (1 3, 20,24,29).…”
mentioning
confidence: 99%
“…8 CBZ-related endocrine changes have been attributed to the induction of the hepatic P450-enzyme system by the drug. 9,10 Oxcarbazepine (OXC), a keto-derivative of CBZ, is a new AED that closely resembles CBZ in structure. 11 However, it has a different metabolic pathway in the liver; instead of by oxidation, it is mainly metabolized by reduction, and does not appear to induce the oxidative P450-enzyme system to the same extent as CBZ.…”
Section: Neurology 2001;56:31-36mentioning
confidence: 99%